Implementing the Kunming-Montreal Biodiversity Targets - John L. Gittleman; Stuart L. Pimm; Berndt J. Van Rensburg; Kyle S. Van Houtan; Callum M. Roberts (Proceedings of the National Academy of Sciences, 2026)
The Kunming-Montreal Biodiversity Targets present the most ambitious and serious conservation agenda ever developed—the overarching goal of preserving 30% of the planet by 2030. An organizational framework is now in place to deliver stable, predictive, and adaptive actions to monitor and measure the Earth’s biodiversity, assess ecological and evolutionary changes, identify key drivers of those changes, and, at the core, apply effective scientific, financial, and governmental treatments to halt biodiversity decline for a sustainable future. Is this implementable? We summarize the essence of the Targets to raise key questions about their execution. We show that the reports of large conservation organizations connect to these Targets only infrequently. Yet, there is abundant evidence to measure the successes and failures of the conservation enterprise. Generally, global financial commitments are substantial and increasing. We specify improvements and continual reassessments toward protected areas, developing countries, and indigenous communities. To achieve success, we recommend actionable plans to improve implementation leading up to and following the next CBD-COP meetings.